2022
DOI: 10.1111/jfs.12976
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antimicrobial effectiveness of synergistic mixtures of rambutan peel extract and cinnamon essential oil on food spoilage bacteria and bio‐based food packaging

Abstract: This research aims to enhance antimicrobial activity of rambutan peel extract (RPE), by mixing with cinnamon essential oil (CEO). The mixture of RPE and CEO with different weight ratios (10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10) had been prepared and the antimicrobial efficacy was tested. Nine strains of bacteria: Gram‐positive bacteria (Bacillus sp., Enterococcus faecalis, Leuconostoc sp., Micrococcus luteus, Staphylococcus aureus, and Streptococcus sp.) and Gram‐negative bacteria (Escheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
(101 reference statements)
1
4
0
Order By: Relevance
“…This was consistent with another study that reported the synergistic effects of a mixture of clove and cinnamon essential oils in increasing antimicrobial efficiency more than by using only one of the essential oils [52]. The bioactive compounds in the mixtures could enhance antimicrobial activity [53]. In addition, silver nanoparticles with gentamicin and zinc oxide with gentamycin synergized the inhibition of S. aureus [54].…”
Section: Synergistic Antibacterial Activity Of Garcinia Mangostana Li...supporting
confidence: 90%
“…This was consistent with another study that reported the synergistic effects of a mixture of clove and cinnamon essential oils in increasing antimicrobial efficiency more than by using only one of the essential oils [52]. The bioactive compounds in the mixtures could enhance antimicrobial activity [53]. In addition, silver nanoparticles with gentamicin and zinc oxide with gentamycin synergized the inhibition of S. aureus [54].…”
Section: Synergistic Antibacterial Activity Of Garcinia Mangostana Li...supporting
confidence: 90%
“…WPI, with a 5:5 ratio of RPE to COE, exhibits excellent synergistic effects against these 9 strains of bacteria due to the improving antimicrobial activity. Moreover, the mechanical and physical properties of the film also improved [48].…”
Section: Malaysia Thailandmentioning
confidence: 94%
“…Moreover, the antimicrobial activity of rambutan peel extract (RPE) can be enhanced by mixing with cinnamon essential oil (CEO), especially when the ratio RPE and CEO was 5:5, the synergist effect against Gram-positive bacterial and Gram-negative bacterial reached the best. The mixture of RPE and CEO is a potential natural antibacterial compound and could be used in food packaging film for prolonging the shelf life of fresh meat and meat products ( Khanoonkon et al., 2022 ).…”
Section: Biological Activitymentioning
confidence: 99%